The Effect of Age of Onset of Bilingualism on Gender Agreement Processing in Spanish as a Heritage Language. Issue 4 (14th July 2022) - Keating, Gregory D.
Abstract: Montrul's (2008) onset age hypothesis predicts that, if attrition occurs in early bilingualism, it will be more severe in simultaneous than in sequential bilinguals. This study tested that prediction in an eye‐tracking experiment focused on the processing of Spanish gender agreement during sentence reading. Heritage Spanish speakers exposed to English at different ages (0–3, 4–6, 7–10 years) read sentences containing violations of noun–adjective gender agreement in 2 distance conditions (adjacent, nonadjacent). Mixed‐effects modeling with reverse Helmert contrasts showed that heritage speakers displayed sensitivity to gender agreement violations in their minority language regardless of onset age and noun–adjective proximity. However, onset age of majority language acquisition determined how early sensitivity manifested itself in the time course of grammatical processing. Consistent with Montrul's hypothesis, sequential bilinguals showed sensitivity to violations earlier in their eye‐movement record than did simultaneous bilinguals. The results suggest onset age can affect grammatical processing in bilinguals who otherwise acquire target like mental representations. Abstract :